INSTITUTIONAL SYSTEMS ENGINEERING FOR RAW MATERIAL SUPPLY OF GELATIN INDUSTRY TO ENSURE PRODUCT QUALITY - Syarifuddin Nur, E. Gumbira-Sa'id, Jono M. Munandar dan Machfud (Jurnal Teknologi Industri Pertanian, 2012)
ABSTRACTIn the provision of product for “halal” quality, there are several criteria that must be met in terms of the types of materials or substances, the procedure of preparation, and how to get it. Products being studied were cattle hides, but these products were not automatically considered as halal products, without a tracking process and standard using applied halal standard. To perform a traceability gelatine raw materials, a system was needed which allows the user to obtain information about the origin of raw materials and the quality process at every stage to the finished products effectively. Tracking system (traceability system) involved several parties, who have different needs and goals in the process of providing raw materials. Therefore, institutional systems engineering was needed to manage the tracking process and bridge the procurement of gelatine raw materials, in order to guarantee the quality of products.  It can be used to facilitate the industry and users to create a gelatine standard quality such as standardization of halal quality. The purpose of this study was to formulate the institutional tracking model of raw material for gelatine industry from cattle hide based on various criteria and assessment of experts. The method used in this study were Interpretive Stuructural Modeling (ISM) to formulate an institutional tracking model of raw material for gelatine industry from cattle hide efficiently, Analytical Hirarchy Process (AHP) to select the traceability strategy of raw materials for gelatine industry, and Data Envelopment Analysis (DEA) to analyze optimal performance of the selected model. The results of this study was the provision of infrastructure and information system for tracking raw materials was needed to ensure product quality and levels of halal products, whereas the model using an independent agency within the quality assurance process, the method of procurement contracts with raw material prices according to quality standards, was the most efficient model.Keywords:  gelatine, institutional model, raw material, traceability, quality supply, cattle hide